Failure mode analysis of two crankshafts of a single cylinder diesel engine. (October 2015) - Fonte, M.; Duarte, P.; Reis, L.; Freitas, M.; Infante, V.
Highlights: Catastrophic failure of two single cylinder diesel engine crankshafts due to misalignment and effect of stress concentrations. Reversed bending on crankpins. Failure mode analysis of two single crankpins. Crack initiation on the crankpin–web fillets and large lubricating oil bore of the crankpin. Abstract: This paper reports an investigation carried out on two damaged crankshafts of single cylinder diesel engines used in agricultural services for several purposes. Recurrent damages of these crankshafts type have happened after approximately 100 h in service. The root cause never was imputed to the manufacturer. The fatigue design and an accurate prediction of fatigue life are of primordial importance to insure the safety of these components and its reliability. This study firstly presents a short review on fatigue power shafts for supporting the failure mode analysis, which can lead to determine the root cause of failure. The material of these damaged crankshafts has the same chemical composition to others found where the same type of fracture occurred at least ten years ago. A finite element analysis was also carried out in order to find the critical zones where high stress concentrations are present. Results showed a clear failure by fatigue under low stress and high cyclic fatigue on crankpins.